Are the criminal procedure constraints experienced by a person properly evaluated during the imposition of a penalty? - Krušinskas, Vidas; Valickas, Liutauras (Vilnius University Open Series, 2024)
The article examines the challenges of ensuring proper protection of human rights, that occur due to criminal procedure constraints, also their evaluation during the implementation of criminal liability (imposition of a penalty). The aim of the study is to thoroughly analyse the evaluation of challenges of ensuring the protection of human rights, caused by the criminal procedure constraints during the implementation of criminal liability. Consequently, various sources of information were examined, including the current legislation, case law, legal doctrine and statistical data. As a result, it was concluded that the realization of the right to criminal proceedings within a reasonable time and the imposition of coercive measures, particularly – of detention, are the most significant aspects of the subject matter. Therefore, person’s right to criminal proceedings within a reasonable time is the most important feature of criminal procedure that is evaluated by the court when implementing criminal liability, while considering not only the factual length of proceedings, but also various other circumstances, consequently, if this right has been violated, the imposed penalty should be reduced or suspended. Meanwhile, the coercive measures imposed during the criminal proceedings are not evaluated as much – detention is the only measure that is taken into account when imposing penalty. The analysis of statistical data has revealed positive trends towards rapid criminal proceedings and rarer detention of suspects. Finally, the conducted survey of law practitioners and theorists revealed that, according to their opinion, the importance of the subject matter is exceptionally significant and it is often desired to change or improve the existing legislation or case law in order to evaluate the constraints of human rights that are experienced by a person during the criminal proceedings more carefully.